POTENSI SUKUK RITEL DAN SUKUK TABUNGAN UNTUK MEMPERCEPAT PEMULIHAN EKONOMI PASCA PANDEMI COVID-19 - Roby Aditiya; Memen Suwandi; Nur Rahmah Sari; Della Fadhilatunisa (Universitas Kuningan, 2022)
AbstractIndonesia as a developing country requires large funds to meet development needs in various sectors. On the other hand, Indonesia is currently experiencing an economic crisis due to the Covid-19 pandemic. As a country with a majority Muslim population, Sukuk as sharia bonds are one of the right choices to meet development financing needs in Indonesia. Sukuk products that have been offered by the Government of Indonesia are Retail Sukuk and Savings Sukuk. The two Sukuk products are sharia investment products that are safe, easy, affordable, and profitable for individual Indonesian citizens. The purpose of this research is to formulate various strategies that can be used to optimize sales of Retail Sukuk and Savings Sukuk. This study uses a literature study with a descriptive qualitative approach. The results of this study formulate several strategies that can be used to optimize sales of Retail Sukuk and Savings Sukuk. These strategies include optimizing the socialization of the millennial generation, conducting sukuk activities to campus, increasing the underlying assets of Retail Sukuk and Savings Sukuk, maintaining competitive returns, tax facilities for investors, and extensification of investors in central and eastern Indonesia.Keywords: Shariah Investment; Ritel Sukuk; Savings Sukuk; Pandemic Covid-19 AbstrakIndonesia sebagai negara berkembang membutuhkan dana yang besar untuk memenuhi kebutuhan pembangunan di berbagai sektor. Di sisi lain, Indonesia saat ini sedang mengalami krisis ekonomi akibat pandemi Covid-19. Sebagai negara dengan mayoritas penduduk muslim, Sukuk sebagai obligasi syariah menjadi salah satu pilihan yang tepat untuk memenuhi kebutuhan pembiayaan pembangunan di Indonesia. Produk Sukuk yang telah ditawarkan oleh Pemerintah Indonesia adalah Sukuk Ritel dan Sukuk Tabungan. Kedua produk Sukuk tersebut merupakan produk investasi syariah yang aman, mudah, terjangkau, dan menguntungkan bagi perorangan warga negara Indonesia. Tujuan penelitian ini ialah untuk merumuskan berbagai strategi yang dapat digunakan untuk mengoptimalkan penjualan Sukuk Ritel dan Sukuk Tabungan. Penelitian ini menggunakan studi kepustakaan dengan pendekatan kualitatif deskriptif. Hasil penelitian ini merumuskan beberapa strategi yang dapat digunakan untuk mengoptimalkan penjualan Sukuk Ritel dan Sukuk Tabungan. Strategi tersebut antara lain mengoptimalkan sosialisasi generasi milenial, melakukan kegiatan sukuk ke kampus, meningkatkan underlying asset Sukuk Ritel dan Sukuk Tabungan, menjaga imbal hasil yang kompetitif, fasilitas perpajakan bagi investor, dan ekstensifikasi investor di Indonesia bagian tengah dan timur.Kata Kunci: Investasi Syariah; Sukuk Ritel; Sukuk Tabungan; Pandemi Covid-19